Determinants of neonatal mortality among newborns admitted in neonatal intensive care unit at Dilla University Referral Hospital in Gedeo Zone, Southern, Ethiopia: unmatched case control study - Atnafu Adem; Azmach Dache; Aregahegn Dona (BMC, 2021)
Abstract Background Around two and half million neonatal mortality occurred in 2017, especially in developing countries. This study was conducted to determine the determinants of neonatal mortality among newborns admitted in the neonatal intensive care unit at Dilla University Referral Hospital in Gedeo Zone, Southern Ethiopia. Methods An unmatched case-control study was conducted from February, 24 to March 6, 2020 at Dilla University Referral Hospital in Gedeo Zone Southern Ethiopia. A total of 304 neonates (76 cases and 228 controls) were involved. Neonates registered as died were considered as cases and neonates registered as improved were considered as controls. Data were extracted by pretested checklists from medical records of neonates admitted during the last one year period. Data was entered into EpiData3.1, and analyzed by statistical package for social science software Version 22.Bivariate and multivariate logistic regressions were used to identify determinants associated with neonatal mortality. Finally, AORs at 95 % CI and P-values < 0.05 were used to declare statistical significance. Results In this study, a total of 304 cases were assessed with 100 % reviewed rate. It was found that referrals from other health facilities, [AORs = 2.43, 95 % CI (1.14, 5.22)], gestational age < 37 weeks,[AORs = 2.50, 95 % CI (1.12, 5.58)], the weight of newborn < 2500 g, [AORs = 2.44, 95 % CI (1.13, 5.28)], neonates positive for sepsis, [AORs = 2.45, 95 % CI (1.11, 5.41)]and neonates who not breastfed within first hour after delivery,[AORs = 5.24, 95 % CI (2.42, 11.37)] were statistically significant determinants to neonatal mortality. Conclusions This study suggests that referral, gestational age, weight of newborn, sepsis and breastfeeding were significant determinants to neonatal mortality. This study shows that neonatal intensive care unit service should be strengthened in Dilla University Referral Hospital; targeting neonate aged below 28 days. Most of these determinants may be prevented and minimized by strengthening referral linkage, improving intrapartum and postpartum care.